Extraction and Chemical Characterization of Functional Phenols and Proteins from Coffee (Coffea arabica) By-Products - Barbara Prandi (MDPI AG, 2021)
Not all the coffee produced goes to the roasting stage, because non-compliant green coffee beans are usually discarded by roasters and the silverskin of the coffee is usually removed and discarded. In the present work, non-compliant green coffee beans and coffee silverskins were fully characterized from a chemical point of view. In addition, enzyme-assisted extraction was applied to recover a fraction rich in proteins and polyphenols, tested for antimicrobial, antityrosinase, and antioxidant activities. Non-compliant green coffee beans showed higher amounts of polyphenols, flavanols, flavonoids, and caffeine than coffee silverskins (which were richer in tannins). The enzymatic extraction of non-compliant coffee green beans produced extracts with a good protein content and with a consistent quantity of polyphenols. The extract showed antioxidant, antityrosinase, and antimicrobial activity, thus representing a promising strategy to recover defective green coffee beans. The antioxidant and antimicrobial activity of coffee silver skins is lower than that of non-compliant coffee green beans extracts, while the antityrosinase activity is comparable.